The deforestation of Easter Island. (10th October 2019) - Rull, Valentí
ABSTRACT: Easter Island deforestation has traditionally been viewed as an abrupt island‐wide event caused by the prehistoric Rapanui civilization, which precipitated its own cultural collapse. This view emerges from early palaeoecological analyses of lake sediments, which showed a sudden and total replacement of palm pollen by grass pollen shortly after Polynesian settlement (800–1200 CE). However, further palaeoecological research has challenged this view, showing that the apparent abruptness and island‐wide synchronicity of forest removal was an artefact due to the occurrence of a sedimentary gap of several millennia that prevented a detailed record of the replacement of palm‐dominated forests by grass meadows. During the last decade, several continuous (gap‐free) and chronologically coherent sediment cores encompassing the last millennia have been retrieved and analysed, providing a new picture of forest removal on Easter Island. According to these analyses, deforestation was not abrupt but gradual and occurred at different times and rates, depending on the site. Regarding the causes, humans were not the only factors responsible for forest clearing, as climatic droughts as well as climate–human–landscape feedbacks and synergies also played a role. In summary, the deforestation of Easter Island was a complex process that was spatially and temporally heterogeneous and took place under the actions and interactions of both natural and anthropogenic drivers. In addition, archaeological evidence shows that the Rapanui civilization was resilient to deforestation and remained healthy until European contact, which contradicts the occurrence of a cultural collapse. Further research should aim to obtain new continuous cores and make use of recently developed biomarker analyses to advance towards a holistic view of the patterns, causes and consequences of Easter Island deforestation.